2011
DOI: 10.1017/s1355617711001147
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition Impairments in Relapsing-Remitting Multiple Sclerosis

Abstract: Theory of Mind (ToM) is the ability to attribute independent mental states to self and others to explain and predict behavior. Impairment of ToM is well established in developmental pathologies. In neurological populations, investigation of ToM is still rare but data suggest that ToM impairment could contribute to behavioral and social disturbances. In addition to neurological signs, multiple sclerosis (MS) presents with disorders of cognition and behavior directly related to brain damage. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
2
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 60 publications
(95 reference statements)
10
92
2
10
Order By: Relevance
“…24 Significant positive correlations have also been reported between both ToM and facial emotion recognition task performance and neurocognitive measures of processing speed, 28,29 working memory, 30,31 and executive function. 28,32 However, the strength and statistical significance of these associations was inconsistent, 25,[28][29][30][31][32][33][34][35] which may be at least partially attributable to differences in task demands. Studies have also reported that social cognition remained significantly impaired among patients with MS even after controlling for neurocognitive performance or after excluding those patients with cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Significant positive correlations have also been reported between both ToM and facial emotion recognition task performance and neurocognitive measures of processing speed, 28,29 working memory, 30,31 and executive function. 28,32 However, the strength and statistical significance of these associations was inconsistent, 25,[28][29][30][31][32][33][34][35] which may be at least partially attributable to differences in task demands. Studies have also reported that social cognition remained significantly impaired among patients with MS even after controlling for neurocognitive performance or after excluding those patients with cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Though depressive symptoms were generally higher in the MS groups, no studies examining ToM reported associations between depressive symptoms and task performance and only 3 assessing facial emotion recognition did so. 31,32,37 Similarly, fatigue was unrelated to performance on ToM tasks 33,35 and evidence linking it to facial emotion recognition was inconsistent. 33,37,38 DISCUSSION Our results show significant deficits in the ability of patients with MS to identify and discriminate between the mental and emotional states of others relative to healthy controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, Ouellet arrived at the conclusion that patients with MS suffering from cognitive deficits tend not to recognize the mental state of others unlike MS patients with preserved cognition (15 cognitively intact and 26 cognitively impaired patients) [49], while Henry (64 patients with relapsing-remitting MS (RRMS), 30 controls) [78] and Pöttgen (45 patients with MS, 45 healthy controls) [21] found that ToM deficits in MS appear independently of the well-known cognitive deficits. Emotion recognition impairments were more pronounced in patients with MS than impairments in thought and intention recognition [21,79].…”
Section: Social Cognition Impairments In Patients With Multiple Sclermentioning
confidence: 99%
“…Despite the great number of studies in social neuroscience investigating patients with acute acquired or neurodegenerative brain damage, research in the field has not yet provided tests that are broad enough for use in the clinic and have focused either on specific pathologies, such as multiple sclerosis [15] or neurodegenerative groups (for review see Henry et al [16]), or alternately, have addressed specifics such as false beliefs [17], or faux pas recognition [14]. Additional global testing, as described earlier, is often too long for clinical practice.…”
Section: Introductionmentioning
confidence: 99%